A routing algorithm for inspecting grid transmission system using suspended robot: Enhancing cost-effective and energy efficient infrastructure maintenance. (10th May 2019) - Nagarajan, Balaji; Li, Yu; Sun, Zeyi; Qin, Ruwen
Abstract: The inspection of transmission line using suspended based robots has drawn great attention from many utility companies. Such an emerging smart technology has the advantages of energy efficiency, cost effectiveness, safety, non-service interruption, and the potential of substituting for the traditional inspection method using linemen with the help of helicopter. In this paper, we propose a routing algorithm to identify locations where the ground control station needs to be deployed when using suspended robot in transmission line inspection. The motion and location between the suspended robot and the ground team are coordinated. The bidirectional data transmission between two sides can be guaranteed so that the live signal can be received and processed, robot motion can be controlled, large size obstacles can be appropriately cleared, and health condition of the transmission line can be captured. A case study based on a segment of the transmission line in the state of Missouri of the United States is implemented to validate the effectiveness of the proposed routing algorithm. Results of the case study illustrate that the performance from both economic and environmental aspects can be significantly improved compared to the traditional inspection mode employing helicopter and linemen as well as an ad-hoc routing algorithm currently used by some utility companies to guide the suspended robot in transmission line inspection. Specifically, compared to the ad-hoc routing algorithm and helicopter with photoelectric stabilized pod, the proposed algorithm can reduce the unit cost by 7.55% and 8.04%; and cut the unit emission by 21% and 98%, respectively.